(untitled) (Asian Journal of Ethnobiology, 2024)
Abstract. Ray TK, Dutta S, Das S, Chakma K. 2024. Ethno-botanical study on medicinal plant species utilized by Marma community of Wagga Union in Rangamati Hill District, Bangladesh. Asian J Ethnobiol 7: 105-114. The utilization of medicinal plant species to cure various health-related ailments is a common practice among the ethnic communities of Bangladesh. This study, conducted in Wagga union of Kaptai upazila, Rangamati hill district, Bangladesh, aimed to document indigenous traditional knowledge (ITK) regarding using ethnomedicinal plants to cure various diseases. The extensive field data collection and various established ethnobotanical survey methods revealed significant findings. The results recorded a total of 53 medicinal plant species belonging to 53 genera and 38 families from the study area, generally used to treat 51 diseases. The family most widely used in the context of the number of medicinal plant species is Asteraceae (9%), followed by Apocynaceae (7%), Amaranthaceae (6%), and Rubiaceae (6%). The research results revealed that leaves are the most widely used plant part (40%) utilized by the local Marma community to make herbal medicine, followed by the whole plant (17%) and roots (14%). The results showed that ethnomedical plants were most widely utilized to treat fever (13.21%) and jaundice (11.32%). This study emphasizes the significance of documenting the indigenous traditional knowledge (ITK) of sustainable natural resource management in biodiversity-rich forest areas, fostering a sense of responsibility and commitment.